A smartphone-based obstacle sensor for the visually impaired - Peng, En; Peursum, Patrick; Li, Ling; Venkatesh, Svetha (Springer-Verlag, 2010)
In this paper, we present a real-time obstacle detection system for the mobility improvement for the visually impaired using a handheld Smartphone. Though there are many existing assistants for the visually impaired, there is not a single one that is low cost, ultra-portable, nonintrusive and able to detect the low-height objects on the floor. This paper proposes a system to detect any objects attached to the floor regardless of their height. Unlike some existing systems where only histogram or edge information is used, the proposed system combines both cues and overcomes some limitations of existing systems. The obstacles on the floor in front of the user can be reliably detected in real time using the proposed system implemented on a Smartphone. The proposed system has been tested in different types of floor conditions and a field trial on five blind participants has been conducted. The experimental results demonstrate its reliability in comparison to existing systems.